Oceanographic and climatic variation drive top‐down/bottom‐up coupling in the Galápagos intertidal meta‐ecosystem. Issue 3 (1st August 2014) - Vinueza, Luis R.; Menge, Bruce A.; Ruiz, Diego; Palacios, Daniel M.
Abstract : The impact of herbivores on primary producers in differing oceanographic regimes is a matter of intense ecological interest due to ongoing changes in their abundance, that of their predators, and anthropomorphic alteration of nutrient cycles and climatic patterns. Interactions between productivity and herbivory in marine habitats have been studied on temperate rocky shores, coral reefs, mangroves, and salt marshes, but less so at tropical latitudes. To determine how herbivore–alga dynamics varied with oceanographic regime, we used the comparative‐experimental approach in rocky intertidal communities on the Galápagos Islands from January 2006 to January 2009. This setting was selected because strongly contrasting oceanographic conditions occurred within a range of ∼181 km, with significant differences in temperature, nutrients, phytoplankton productivity, and intertidal communities, and in abundance of macro‐herbivores, including marine iguanas. Experiments and measurements were conducted at two sites in each of three oceanographic regimes characterized by low, intermediate, and high bottom‐up inputs. At sites of low inputs, macro‐herbivores (fish, crabs, iguanas) had a consistent top‐down effect, reducing algal abundance, and leaving a few grazer‐resistant varieties. At sites of intermediate and high inputs, consumer impacts were stronger during La Niña (cool phase) than during El Niño (warm phase). At sites of high inputs, algal biomass was naturally relatively high and was dominated by the edible algae Ulva spp. Macro‐grazers reduced algal biomass, but their primary effect was indirect, as articulated corallines displaced other species of algae in their absence. Prior results from the tropics had revealed dominant effects of top‐down interactions and recruitment in structuring intertidal communities. Our results suggest that, when a broader oceanographic scenario is taken into account, the relative importance of top‐down and bottom‐up forces are context dependent, varying with oceanographic regime and climatic variability.